Menulis Akademis Bantuan AI: Mula-mula Diantisipasi Tetapi Sekarang Sudah Tidak Terbendung, Akhirnya Menyisakan Wilayah Abu-abu - Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2026)
The presence of AI in academic writing was initially anticipated, but its progress has been unstoppable, ultimately creating a gray area. This study aims to answer the question of how AI can be utilized in academic writing without violating ethics, security, and academic integrity. This study uses a qualitative approach by applying a literature review method. The results show that AI is capable of producing academic writing independently that can be verified as equivalent to the capabilities of human scientists. This paper has discussed the conflict between advocates of AI ethics and AI safety and AI accelerators, including the AI ​​dilemma and gray areas. The conclusion of this study is that understanding AI-generated text can maintain academic integrity.